The Working Class Culture in Bursa - Şenol Baştürk; Kemal Temel (Journal of Economy Culture and Society)
The steady increase in the number of wage earners in Turkey during the last 20 years has brought social expansion of middle-class and working-class groups to the agenda. In the relevant period, forms of labor market stratification became more visible. Widespread flexibility practices, such as subcontracting, have diminished secure employment. The emergence of new types of employment, especially the expansion of employment in the service sector, has also significantly affected social structure transformations. Studies that addressed developments in social transformation from class-cultural perspective have focused more on middle-class groups. This study examines Turkish working-class culture from a class-cultural perspective. Adopting a neo-Bourdieusian class approach, this study analyses the transformations in lifestyles, tastes and voting behaviors of the working class in three different regions of Bursa. The study claims that different social and material conditions of existence spatially differentiate working-class culture. The results of the survey research conducted in Bursa in 2022 were analyzed by multiple correspondence (MCA) analysis. The results of this research show that independent variables such as workers’ social background, education level, material earnings and differences in property relations construct spatial and cultural differentiation.